Relevance of Action Research in the Vindication of the Sense of the Human in Scientific Administration - Escobar Escobar, María Beatriz (2024)
Action research is a historical, intellectual and methodological field that, transferred to scientific administration, allows it to listen to the word of the other, based on an introspective inquiry that highlights the ideological and political commitment of those involved in the process of knowledge construction. the aim is to describe the relevance of action research in the vindication of the sense of the human in scientific administration. This is a documentary research in scientific databases such as EBSCO and ProQuest Central and academic search engines such as Google Academic Search Engine, Bielefeld Academic Search Engine, DOAJ and ERIC. The theoretical corpus is deployed on two relevant categories from which it is possible to access a historical understanding of the method. The first level recognizes its validity and importance as a research tradition, while the second emphasizes the preponderance of reflective thinking and the search for subjectivity as necessary inputs to read, perceive, form, know and transform the reality of the people who participate in the research and administrative work.